The Tellability of Police Use-of-force: How Police Tell Stories of Critical Incidents in Different Contexts. (14th February 2017) - Schaefer, Brian P; Tewksbury, Richard
Abstract: Critical incidents involving police use-of-force brings forth external critique to the police institution and to police officers. Building on previous research on ideas of emotions and tellability, the present paper examines the role of police storytelling of critical incidents in different spaces. Stories of critical incidents told by police focus on reinforcing the police's singular right to use force and to interpret use-of-force events. However, stories in the canteen do not question police action and seek to separate out officers who fail to support the in-group, while stories in the squad car provide space for confidants to privately critique these events and provide a more nuanced view of use-of-force. The study concludes by discussing the implications of the findings.